Impact of post-colposcopy management on women's long-term worries: results from the UK population-based TOMBOLA trial. Issue 1 (16th September 2015) - Sharp, Linda; Cotton, Seonaidh; Cruickshank, Margaret; Gray, Nicola; Smart, Louise; Whynes, David; Little, Julian
Abstract : Background: Effective cervical screening reduces cancer incidence and mortality. However, these benefits may be accompanied by some harms, potentially including, adverse psychological impacts. Studies suggest women may have concerns about various specific issues, such as cervical cancer. Aim: To compare worries about cervical cancer, future fertility, having sex, and general health between women managed by alternative policies at colposcopy. Design: Multicentre individually-randomised controlled trial, nested within the National Health Service Cervical Screening Programmes. Setting: UK. Methods: 1515 women, aged 20–59 years, with low-grade cytology who attended colposcopy during February 2001–October 2002, were randomised to immediate loop excision or punch biopsies with recall for treatment if cervical intraepithelial neoplasia (CIN)2/3 was confirmed. Women completed questionnaires at recruitment and after 12, 18, 24 and 30 months. Outcomes were prevalence of worries at each time-point (point prevalence) and at any time-point during follow-up (12–30 months; cumulative prevalence). Primary analysis was by intention-to-treat (ITT); secondary per-protocol analysis compared groups according to management received among women with an abnormal transformation zone. Results: Cumulative prevalence of worries was: cervical cancer 40%; having sex 26%, future fertility 24%, and general health 60%. In ITT analyses, there were no statistically significant differences between management arms in cumulative or point prevalence of any of the worries. In per-protocol analyses, between-group differences were significant only for future fertility; cumulative prevalence was highest in women who underwent punch biopsies and treatment. Conclusions: There is no difference in the prevalence of specific worries in women randomised to alternative post-colposcopy management policies. Clinical trial registration: ISRCTN:34841617.